Clinical leadership training: an evaluation of the Welsh Fellowship programme. Issue 2 (23rd April 2018) - Phillips, Suzanne; Bullock, Alison
Abstract : Purpose: UK fellowship schemes have been set up to address low-level engagement of doctors with leadership roles. Established in 2013, the Welsh Clinical Leadership Fellowship (WCLF) programme aims to recruit aspiring future clinical leaders and equip them with knowledge and skills to lead improvements in healthcare delivery. This paper aims to evaluate the 12-month WCLF programme in its first two years of operation. Design/methodology/approach: Focused on the participants ( n = 8), the authors explored expectations of the programme, reactions to academic components (provided by Academi Wales) and learning from workplace projects and other opportunities. The authors adopted a qualitative approach, collecting data from four focus groups, 20 individual face-to-face or telephone interviews with fellows and project supervisors and observation of Academi Wales training days. Findings: Although from diverse specialties and stages in training, all participants reported that the Fellowship met expectations. Fellows learned leadership theory, developing understanding of leadership and teamwork in complex organisations. Through workplace projects, they applied their knowledge, learning from both success and failure. The quality of communication with fellows distinguished the better supervisors and impacted on project success. Research limitations/implications: Small participant numbers limit generalisability. The authors did not evaluate longer-term impact. Practical implications: Doctors are required to be both clinically proficient and influence service delivery and improve patient care. The WCLF programme addresses both the need for leadership theory (through the Academi Wales training) and the application of learning through the performance of leadership roles in the projects. Originality/value: This work represents an evaluation of the only leadership programme in Wales, and outcomes have led to improvements.